Assessing Leading Coach Behavior of Elite Karate Athletes (Sample of Kocaeli Gebze) - Altan, Fatma; Bayazıt, Betül (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
In every profession, sports require leaders who can enhance athlete performance, foster positive behaviors during training and competitions, and guide them towards appropriate objectives. This study examined the coaching behavior styles in a club that trains successful athletes. The study employed a "descriptive survey" model, which is a type of quantitative research. The research was performed by participants involved in individual and team sports (n=107). 107 athletes were contacted in a club comprising 140 elite athletes. This study aimed to ascertain the predominant coaching behaviors-democratic, laissez-faire, and autocratic-employed by coaches at the Şamdan Karate Do Sports Club in Gebze, known for training Turkey's most successful karate athletes. In our study, we employed T-tests for independent groups and one-way analysis of variance among parametric tests. The average scores of participants in the autocratic sub-dimension of the scale surpassed those of the other leadership styles. In this evaluation scale of coaches by athletes, it was noted that the majority of athletes reported working with an autocratic coaching style, characterized by the coach's total control and the athletes' passive role. The average scores for the alternative leadership styles in the study are in the moderate range. Based on the average scores in the sub-dimensions, it can be concluded that the participants' assessment of the leader coach is at a moderate level. This suggests that the coaching behaviors at the successful Şamdan Karate Do sports club differ based on the athletes' characteristics, indicating the application of multiple leadership styles rather than a singular approach.